2012
DOI: 10.1177/0001839212466521
|View full text |Cite
|
Sign up to set email alerts
|

Fatherhood and Managerial Style

Abstract: Motivated by a growing literature in the social sciences suggesting that the transition to fatherhood has a profound effect on men’s values, we study how the wages of employees change after a male chief executive officer (CEO) has children, using comprehensive panel data on the employees, CEOs, and families of CEOs in all but the smallest Danish firms between 1996 and 2006. We find that (a) a male CEO generally pays his employees less generously after fathering a child, (b) the birth of a daughter has a less n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Regarding the gender of children, previous research has found evidence that behavioural changes of parents evolve differently. For example, CEOs with daughters are said to be more other-oriented (Dahl et al, 2012). We cannot exclude that also leadership behaviours evolve differently depending on the gender constellation of the offspring.…”
Section: Limitationsmentioning
confidence: 99%
“…Regarding the gender of children, previous research has found evidence that behavioural changes of parents evolve differently. For example, CEOs with daughters are said to be more other-oriented (Dahl et al, 2012). We cannot exclude that also leadership behaviours evolve differently depending on the gender constellation of the offspring.…”
Section: Limitationsmentioning
confidence: 99%
“…This is surprising, as one would expect self-eval- uation to be more critical than observers' assessment (Posner, 2016). We interpret the high levels of perceived improvement in relations-oriented TLB as being due to generally increased orientation of leaders towards others (Dahl et al, 2012). On the other hand, a low level of perceived improvement of external-oriented TLB should have its cause in reduced time availability and attention, focus shift and a willingness to spend time for extra-professional affairs (Stellner, 2021).…”
Section: Contributionmentioning
confidence: 64%
“…Fatherhood is said to act as a catalyst for personal development, and changes one's societal role, self-construal and priorities. It is regarded as one of the most momentous events in a man's life, with the potential to realign person-al values (Dahl et al, 2012). Nevertheless, this transition process of parenthood in general and specifically its effects on personality and behaviour have received little attention in research so far (Bleidorn et al, 2016;van Scheppingen et al, 2016).…”
Section: Fatherhood Rolementioning
confidence: 99%
“…We need to point out that we are not the first to show no clear support for the daughter effect (Lee and Conley, 2016;however, see Hopcroft (2016) for a methodological comment on that particular finding). Moreover, in one study, Dahl et al, (2012), showed that the birth of a child (even daughters, if the first-born child was not female) makes male CEOs less generous to employees.…”
Section: Discussionmentioning
confidence: 99%